Age estimation in young dogs by radiographic assessment of the canine pulp cavity/tooth width ratio. (1st February 2022) - Van den Broeck, Martine; Stock, Emmelie; Vermeiren, Yoni; Verhaert, Leen; Duchateau, Luc; Cornillie, Pieter
Abstract: Age estimation in adult dogs can be performed by the radiographic measurement of the tooth pulp cavity, but the technique has hardly been described. In this study, the application of measuring pulp/tooth width ratios (P/T ratios) of the maxillary canine teeth was investigated. Pulp and tooth widths were measured at two locations on 166 maxillary canine teeth of the heads of 84 dog cadavers, using digital extraoral lateral oblique open mouth radiographs. The dogs belonged to different breeds and sexes and had a known age between 194 and 1907 days (approximately 6 months ‐ 5 years). Both at the cemento‐enamel junction (CE) and the half‐height of the tooth, a comparable non‐linear regression with age was demonstrated. Measuring at the CE location was less hindered by wear or superimposition. No statistically significant difference according to sex and breed size and no clinically significant difference according to skull type was found. The highest predictable capacity was found in the youngest dogs until the age of 448 days, of which 84.4% of the canine teeth had a P/T ratio above 0.39. Our results demonstrate that measuring P/T ratios of canine teeth can be used in practice to assign dogs to age categories, with the highest accuracy in young adult dogs.